Accounting Comparability and the Accuracy of Peer-Based Valuation Models - Young, Steven; Zeng, Yachang (The Accounting Review, 2015)
ABSTRACT We examine the link between enhanced accounting comparability and the valuation performance of pricing multiples. Using the warranted multiple method proposed by Bhojraj and Lee (2002), we demonstrate how enhanced accounting comparability leads to better peer-based valuation performance. Empirical tests using firms from 15 European Union (EU) countries over the period 1997–2011 (with comparable peers selected from the entire cross-section of foreign firms) document significant improvement in valuation performance measured as pricing accuracy, the ability of value estimates to explain cross-sectional variation in observed price, and the ability of the pricing multiple to predict future market-to-book multiples. Findings for a series of identification tests suggest that enhanced valuation performance is the consequence of improvements in the degree of cross-border accounting comparability that occurred during the sample window, and that a significant fraction of comparability gain operates through improved peer selection.